Enslaved africans in the cocoa expansion of Ilhéus-Bahia, 1850-1888 - Andrade, Marcelo Loyola de (Sankofa (São Paulo), 2022)
This article analyzes the enslaved Africans in Ilhéus, southern Bahia, between the years 1850 and 1888, the period of expansion of the cocoa crop. It focuses on the economic activities engaged and the demographic characteristics of the population. The privileged sources are postmortem inventories and the 1872 General Census of the Empire of Brazil. The main view emphasizes the situations of vulnerability imposed very often, involving exploitation of labor and the many families dismantling through sales and donations, when dividing goods among heirs. In this context, ordinarily treated as commodities, they reacted in several ways.